Volcanoes Geological and Geophysical Setting, Theoretical Aspects and Numerical Modeling, Applications to Industry and Their Impact on the Human Health - Aiello, Gemma (IntechOpen, 2018)
This book contains 12 chapters dealing with the studies on volcanoes, their geological and geophysical setting, the theoretical aspects and the numerical modeling on volcanoes, the applications of volcanoes to the industry, and the impact of volcanoes on the human health, in different geological settings and using several techniques and methods, including the volcanology, the seismology, the statistical methods to assess the correlation between seismic and volcanic activity (modified Ripley's K-function to regional seismicity), the field geological survey of volcanic successions, the analytical methods of petrologic analysis, the petrography of the volcanic rocks with the individuation of the modal compositions of volcanic rocks and their comparison with major elements and trace elements in variation diagrams, and the argon isotopic measurements performed through the peak height comparison (unspiked) method. The oceanographic methods have also been applied to case studies of submarine volcanic edifices located in the Canary Islands (Atlantic Ocean), including the sampling of the water column with a conductivity-temperature-depth (CTD) sensor rosette with 24 Niskin bottles, in order to determinate key physical and chemical parameters, such as the total-scale pH, the total dissolved inorganic carbon (C), the total alkalinity (A), the temperature, the salinity, and the dissolved oxygen. Problems of volcanic risk mitigation have also been treated, regarding the eruption disasters in Indonesia, a country where a high number of people live next to the volcanoes, and characterized by the lack of public awareness of the eruption disasters. Petrographic methods have been successfully applied to the study of the Cretaceous magmatism of the layered gabbroids of the Chukotka region (Pekulney Ridge, Russia), and geodynamic implications have been successfully established through geological and petrographic studies. The relationships among the mantle wedge, the convective heat and mass transfer, the infiltration metasomatism, the zoning, and the mathematical models have been applied to the comprehension of complex volcanic areas through the theoretical aspects of volcanic studies on magmatic chambers coupled with numerical modeling, including finite element models (FEMs) in the individuation of volcanic deformations.